2020
DOI: 10.3390/su122410354
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Stakeholders’ Views on Technology Integration: The Role of Educational Leadership for Sustainable Inclusive Education

Abstract: This study aims to determine the views of teachers, school administrative staff having educational leadership roles, and faculty members on integration of technology and the role of educational leadership for sustainable inclusive education. The study group included 38 teachers working in Mersin province, Turkey, 11 school administrative staff, and 11 faculty members working at the Education Faculty. This study was structured employing a “basic interpretive qualitative study model”. In the study, a semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Malaysia's Ministry of Higher Education's drive toward Education 4.0, Uygur et al (2020) found that the technology-based literature on education to meet the learning styles of today's tech-savvy generation is still quite limited.…”
Section: Data Findings and Discussionmentioning
confidence: 99%
“…Malaysia's Ministry of Higher Education's drive toward Education 4.0, Uygur et al (2020) found that the technology-based literature on education to meet the learning styles of today's tech-savvy generation is still quite limited.…”
Section: Data Findings and Discussionmentioning
confidence: 99%
“…In this line, Yazdani et al (2023) emphasize the importance of considering factors such as the way knowledge is generated and transmitted, and the development of skills in the face of the demands of society. Also, Uygur et al (2020) argue that for the use of EdTech to promote sustainable inclusive education effectively, teachers must first be trained and receive appropriate support.…”
Section: Framework For the Development Of Qe Through Edtechmentioning
confidence: 99%
“…Additionally, online learning has some Learners' Expectations towards Virtual Learning and its … International Journal of Instruction, January 2024 • Vol.17, No.1 shortcomings related to learners or instructors (Kebritchi et al, 2017;Murugaiah & Yen, 2019;Nortvig et al, 2018) however the disparity between online learning and the expectation of students may affect their learning performance (Newlands & Coldwell, 2005). Several factors may affect to students perform in online classes such as parental education, students' geographical locations of schools and their homes (Westbrook, 2014) whereas the lack of infrastructure and resources, diverse teaching strategies (Mupinga et al, 2006), and negligence of concerned stakeholders (Blömer et al, 2020;Uygur et al, 2020) have created barriers to virtual learning. Kunwar et al (2020) also showed that students' expectations, changing role of tutors, lack of effective communication, and practices of digital pedagogy are issues for the promotion of online education in Nepal.…”
Section: Introductionmentioning
confidence: 99%